The Effect of Mergers on Financial Performance PT. Bank Woori Saudara Indonesia 1906, Tbk - Irna Maulana; Gemala Paramita; Syahiruddin Syahiruddin (Ilomata International Journal of Management, 2019)
The Mergers are carried out by the companies to get a number of benefits. Mutually beneficial conditions will occur if the merger activities carried out can create the synergy, which finally, it is expected to improve the company's performance. This study aims to determine whether the financial performance after the merger has changed or not. The financial ratios studied are financial ratios four years after the merger and before the merger. This research was conducted by quantitative methods, by taking data from PT. Bank Woori Saudara Indonesia 1906, Tbk, which has merged in 2014 and has engaged in banking financial services. Sampling in this study uses quota sampling. the data is obtained from one bank, that is, a bank which has merged. The parametric test used to answer the hypothesis in this study was the Paired Sample T-Test. The results of this study indicate that in partial testing of the seven financial ratios, there was a significant difference in the ratio of BR and EPS, while the CAR, TATO, NPM, ROI, and ROE ratios showed no significant differences. So the merger process carried out by banks does not show a significant difference because the synergy has not yet been achieved after the merger.